Store And Product Characteristics In The Formation Of Consumer Impulse Buying - A. Aminartha Putri, Deasy Soraya; Arfianty , Arfianty (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Consumer behavior has always been a prominent topic in marketing because understanding how and why consumers act in certain ways and make purchasing decisions helps companies to develop more effective marketing strategies. The purpose of this study is to analyze the relationship between store characteristics and product characteristics, both partially and simultaneously, on impulsive buying at Toko XYZ, Parepare city.The objectives of this study are to examine the income of palm sugar businesses, identify the economic potential of sugar palm cultivation, and assess its prospects for improving community welfare. The analytical methods used in this study include validity tests, reliability tests, classical assumption tests (normality test, multicollinearity test, and heteroskedasticity test), multiple regression analysis, and hypothesis testing, consisting of correlation coefficient, coefficient of determination, partial test, and simultaneous test. The findings of this study reveal that store characteristics have a positive and significant partial effect on impulsive buying at Toko XYZ in Parepare city. In contrast, product characteristics show a negative and significant partial effect on impulsive buying, indicating that certain product attributes may reduce consumers’ unplanned purchasing decisions. However, when examined simultaneously, both store characteristics and product characteristics jointly demonstrate a positive and significant effect on impulsive buying. These results imply that although product characteristics individually may discourage impulsive purchases, the overall combination of store environment and product attributes still contributes to increasing consumers’ impulsive buying behavior at Toko XYZ.